The theory and practice of criminal justice in Africa - Chikwanha, Annie Barbara ([Tshwane (Pretoria) : Institute for Security Studies, 2009)
In Africa, criminal justice systems remain rather fragile. This is n ot only because of the human rights practices of some African governmen ts, but because the changes on the continent demand good governance and democracy. Criminal justice cannot be separated from democracy in as m uch as its effective implementation has become a barometer of democrati c practices throughout the developed world. Africa's deficiencies in th e criminal justice system can benefit from a comprehensive scrutiny not just of the technical legal issues, but of the ethical issues too, as well as the dissection of international norms, institutions and crimina l justice processes and their relevance for Africa. This monograph undo ubtedly makes a significant contribution to the fledging criminological writings on the African continent and all the articles reveal the chal lenges the criminal justice systems in Africa have to overcome in order to fulfill their commitments to international standards and norms.
June 2009
Includes bibliographical references.
Keywords: Criminal justice, Administration of -- Africa; Criminal courts -- Africa; Criminal procedure -- Africa; Human rights -- Africa